2020
DOI: 10.3332/ecancer.2020.1025
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and mortality trends in Metropolitan Lima young adults, 1990–2012

Abstract: Aims: The purpose of this research was to calculate and compare standardised incidence and mortality ratios in young adults, based on the data published by the population-based cancer registry of Metropolitan Lima. Method: A secondary analysis was carried out on the data published by the population-based cancer registry of Metropolitan Lima in its last five volumes. Calculating the standardised incidence ratio, in accordance with the World Health Organization's standard population, was done using the direct me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In a study focused on the young population of Lima, it stands out that among the tumors with the highest mortality in men is lung cancer. A segment where this diagnosis is not so common (Luna-Abanto and Ruiz et al, 2020) Although Latin America has implemented effective control measures against tobacco (Burki, 2017), there is still room for improvement, especially in the provinces with smoking prevalence as high as 50%. For this reason, Peru should implement public health programs to lower smoking prevalence, with the final aim to reduce the morbidity and mortality of lung cancer (Pichon-Riviere and Bardach et al, 2016), and reduce the financial impact of smoking on the health system in Peru (Pichon-Riviere and Bardach, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a study focused on the young population of Lima, it stands out that among the tumors with the highest mortality in men is lung cancer. A segment where this diagnosis is not so common (Luna-Abanto and Ruiz et al, 2020) Although Latin America has implemented effective control measures against tobacco (Burki, 2017), there is still room for improvement, especially in the provinces with smoking prevalence as high as 50%. For this reason, Peru should implement public health programs to lower smoking prevalence, with the final aim to reduce the morbidity and mortality of lung cancer (Pichon-Riviere and Bardach et al, 2016), and reduce the financial impact of smoking on the health system in Peru (Pichon-Riviere and Bardach, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, no significant correlation was found between the incidence rate and RSV (Rho: 0.098; p: 0.640). Incidence and mortality studies revealed that these rates have remained in the first places for the evaluated regions, while they decreased in metropolitan Lima [34,35], this could be related to the access to health and Internet. Cervical cancer continues to be one of the main causes of morbidity and mortality in Peru, in this sense it would be valid to consider an awareness strategy targeting women in high prevalence areas, using digital media, which have shown to increase interest in cervical cancer knowledge and prevention [8,[36][37][38] Figure 1(c) and Figure 2(c).…”
Section: Cervical Cancermentioning
confidence: 99%
“…Researches gradually focused on this treatment even with encouraging results especially in very selected patients with a concomitant R0 cytoreductive surgery with an OS of 50.1 months significantly compared to patients that received only cytoreductive surgery without LR (61). There are few studies that demonstrated the safety of LR with no mortality within 30 days (62)(63)(64).…”
Section: Ovarianmentioning
confidence: 99%